Causes of Crime - Andrzej Klimczuk (The SAGE Encyclopedia of Economics and Society, 2015)
Causes of crime are the subject of the etiology of criminal behavior, which is characterized by an interdisciplinary approach. There are many theories attempting to explain the determin ants of criminal behavior, a set of acts recognized by the criminal law, which emphasize different aspects of this phenomenon.
Keywords: A19; Z13; 300; Crime; public policy